Ответ:
26
Объяснение:
Вот......................
5m³ - 3n² + 2mn - 8m³ - mn + 7n² = (5-8)m³ + (-3+7)n² + (2-1)mn = -3m³ + 4n² + mn
Если n = 1; m = -2, то:
-3m³ + 4n² + mn = -3 * (-2)³ + 4 * 1² + (-2) * 1 = 24 + 4 - 2 = 26
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
26
Объяснение:
Вот......................
5m³ - 3n² + 2mn - 8m³ - mn + 7n² = (5-8)m³ + (-3+7)n² + (2-1)mn = -3m³ + 4n² + mn
Если n = 1; m = -2, то:
-3m³ + 4n² + mn = -3 * (-2)³ + 4 * 1² + (-2) * 1 = 24 + 4 - 2 = 26